Does Dietary Adequacy Reflect the Cognitive Performance of Children? A Study among the Homeless Children in Klang Valley, Malaysia - Chin, K. J.; Asma, A.; Yusof, H. M.; Churak, P.; Latiffah Karim (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by Scopus